Quality of Life and Functioning Impairments Across Psychiatric Disorders in Adults Presenting for Outpatient Psychiatric Evaluation and Treatment - Waguih William IsHak; James Mirocha; Jonathan Dang; Brigitte Vanle; Benjamin Metrikin; Kaleab Tessema; Itai Danovitch (Psychiatric Research and Clinical Practice)
Objective Psychiatric disorders are associated with impairments in quality of life (QOL) and functioning. What remained to be investigated was the comparison of these constructs across psychiatric disorders in treatment‐seeking adults. It was hypothesized that mood disorder patients would endorse worse QOL and functioning at entry into psychiatric outpatient treatment compared to patients with other disorders, and that regardless of diagnosis, severe impairments in QOL and functioning would be endorsed by the majority of the sample (>70%). Methods Data were collected for 2114 adults. Diagnostic and Statistical Manual of Mental Disorders diagnoses were obtained using the Mini International Neuropsychiatric Interview. Patients completed measures of QOL (Q‐LES‐Q), functioning (Work and Social Adjustment Scale [WSAS], Sheehan Disability Scale, Endicott Work Productivity Scale), and depression (Quick Inventory of Depressive Symptomatology‐Self Report). Results Overall, 70.6% of patients with psychiatric disorders reported severe impairment in QOL and 59.6% of patients reported severe impairment in functioning (per the WSAS). Patients with mood disorders were more likely to report severe impairments in QOL and functioning, compared to patients with other psychiatric disorders. Analysis of variance revealed patients with mood disorders reported significantly lower QOL, worse functioning, and greater depressive symptom severity compared to patients without mood disorders (all p values <0.05). Conclusions Patients with psychiatric conditions overwhelmingly reported severely impaired QOL and functioning at entry to outpatient treatment. Patients with mood disorders were disproportionately more likely to endorse severely impaired QOL and functioning, particularly those with Major Depressive Disorder, recurrent, and Bipolar Disorder I, depressive episode. Findings suggest that future treatment efforts should focus on interventions that restore QOL and functioning in psychiatric patients, particularly among those with mood disorders.